Mutation m.3395A > G in MT-ND1 leads to variable pathologic manifestations. (3rd February 2020) - Gutiérrez Cortés, Nicolás; Pertuiset, Claire; Dumon, Elodie; Börlin, Marine; Da Costa, Barbara; Le Guédard, Marina; Stojkovic, Tanya; Loundon, Natalie; Rouillon, Isabelle; Nadjar, Yann; Letellier, Thierry; Jonard, Laurence; et al.
Abstract: A non-synonymous mtDNA mutation, m.3395A > G, which changes tyrosine in position 30 to cysteine in p.MT-ND1, was found in several patients with a wide range of clinical phenotypes such as deafness, diabetes and cerebellar syndrome but no Leber's hereditary optic neuropathy. Although this mutation has already been described, its pathogenicity has not been demonstrated. Here, it was found isolated for the first time, allowing a study to investigate its pathogenicity. To do so, we constructed cybrid cell lines and carried out a functional study to assess the possible consequences of the mutation on mitochondrial bioenergetics. Results obtained demonstrated that this mutation causes an important dysfunction of the mitochondrial respiratory chain with a decrease in both activity and quantity of complex I due to a diminution of p.MT-ND1 quantity. However, no subcomplexes were found in cybrids carrying the mutation, indicating that the quality of the complex I assembly is not affected. Moreover, based on the crystal structure of p.MT-ND1 and the data found in the literature, we propose a hypothesis for the mechanism of the degradation of p.MT-ND1. Our study provides new insights into the pathophysiology of mitochondrial diseases and in particular of MT-ND1 mutations.